The use of small-sided games as an aerobic fitness assessment supplement within elite level professional soccer - Owen, A. L.; Newton, M.; Shovlin, A.; Malone, S. (Journal of Human Kinetics, 2020)
The purpose of this investigation was to quantify the association between 5 vs. 5 small sided games (SSG) running performance and physiological performance during the Yo-YoIR1 test to ascertain the utility of SSGs as a potential fitness test modality within elite professional soccer players. Twenty-three (n = 23) elite male professional soccer players (mean ± SD age 25.3 ± 3.1 yrs, mass: 76 ± 9 kg, height: 176 ± 9 cm) were assessed. Players completed an intermittent aerobic fitness test (Yo-YoIR1) and a 5 vs. 5 SSGs protocol for the purpose of the study. During all SSGs players wore GPS (Statsports 10-Hz, Viper Pod, Newry, Northern Ireland) and HR monitors (Polar, Oy Kemple, Finland) with these measures related to Yo-YoIR1 running performance. Results revealed SSGs running performance (TD; m) and physiological performance (HR) showed the lowest CV% (< 5%), with high speed movements, accelerations and decelerations highlighting higher CV% during SSGs. Possibly small to possibly very large associations were observed for running performance during 5 vs. 5 SSGs and Yo-YoIR1 performance, with negative associations observed between physiological performance during SSG and YoYoIR1 running performance. To conclude, the current study observed how running performance during a standardised 5 vs. 5 SSG protocol within elite soccer cohorts is associated with the Yo-YoIR1 running performance. Given the low CV%, repeatability and large association of global running performance and internal load measures during a 5 vs. 5 SSG with Yo-YoIR1 performance, this particular soccer specific SSG protocol potentially supplements traditional non-sport specific testing assessments.